1994
DOI: 10.1016/0140-7007(94)90010-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suction-line/liquid-line heat exchange in the refrigeration cycle

Abstract: ABSTRAcrThe paper presents a theoretical evaluation of the performance effects resulting from the installation of a liquid line! suction line heat exchanger (llsl·hx). It examines cycle the parameters and refrigerant thermodynamic properties that determine whether the installation results in improvement of COP and volumetric capacity. The study showed that the benefit of application of the Jlsl-hx depends on a combination of operating conditions and fluid properties • heat capacity, latent heat, and coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 3 publications
2
58
0
3
Order By: Relevance
“…This reduction was mainly Nonetheless, the use of the IHX with a combination of a gas-cooler in the CO cycle, reductions from 1.8 to 3.29 % were measured at -25 ºC of evaporation temperature, but small improvements up to 0.45 % were observed at -40 ºC. 2 Accordingly, it can be concluded that despite the reductions of capacity and COP in the CO subcritical cycle resulted in reductions of the heat to be transferred in the cascade condenser, reductions which were more important at low evaporating levels. This reductions of the heat transferred to the high temperature cycle in cascade systems produced increments on the COP of the cascade system from 0.15 to 2.91 %.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This reduction was mainly Nonetheless, the use of the IHX with a combination of a gas-cooler in the CO cycle, reductions from 1.8 to 3.29 % were measured at -25 ºC of evaporation temperature, but small improvements up to 0.45 % were observed at -40 ºC. 2 Accordingly, it can be concluded that despite the reductions of capacity and COP in the CO subcritical cycle resulted in reductions of the heat to be transferred in the cascade condenser, reductions which were more important at low evaporating levels. This reductions of the heat transferred to the high temperature cycle in cascade systems produced increments on the COP of the cascade system from 0.15 to 2.91 %.…”
Section: Resultsmentioning
confidence: 99%
“…In the evaporator, the cooling capacity provided by the cycle, Equation (1), was contrasted with the heat transfer rate of the secondary fluid, Equation (2). Their difference in average was of 2.4 % working without IHX and of 3.3 % with IHX.…”
Section: Experimental Procedures and Data Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…While all refrigerants theoretically can reach similar efficiencies with sufficient cycle modification and optimization (Domanski et al, 1994;Domanski, 1995), each element of added complex-ity increases costs, refrigerant charge (amount), the potential for leaks, and thermodynamic irreversibility's and decreases reliability (Calm and Didion, 1997). Hence, refrigerants with high efficiencies in simple cycles have an inherent advantage to improve efficiencies at lower costs and with lower system risk of environmental harm.…”
Section: International Journal Of Advances In Scientific Research Andmentioning
confidence: 99%